Digital climate information and advisory services for de-risking aquatic food systems - Hossain, Peerzadi; Ahmed, Raju; Barman, Benoy (WorldFish, 2023)
Bangladesh’s aquaculture and fisheries sector are highly vulnerable to climate change, variabilities and extremes. It is imperative to identify climate risks, sensitive operations and management decisions for each value chain and, accordingly, to develop contextualized advisory services using timely and reliable climate information for managing associated climate risks. Furthermore, the government’s digital Bangladesh portfolio directs the country’s vision 2041 to consider the whole of society approach in digital form. Hence, the main objective of this policy brief is to flag recent research and interventions on Digital Climate Information and Advisory Services for aquatic food systems to make climate-informed decisions and to mainstream those in the upcoming revision process for the country’s 1998 national fisheries policy. These research results can help create a timely policy instrument to de-risk aquaculture value chains, improve adaptation to climatic stressors and, thus, build climate resilience.